Keluarga Sejahtera dalam Gereja Katolik dan Islam: Studi Tentang Tujuan Perkawinan dalam Gereja Katolik dan Islam - Parhusip, Bintang; Situmorang, Kalaudius Willy (Perspektif, 2023)
The focus of the writer is the purpose of marriage in the Catholic Church and Islam. These two major religions have the goal of marriage which describes the achievement of a prosperous household life. This prosperity certainly has many factors and is not only tied to one side. This is considered important because it is directly related to the real life of marriage. The purpose of writing this study is to explore the purpose of marriage in the Catholic Church and also in Islam. Both are seen together and look for what is the essence of both. By knowing their views on the purpose of marriage the writers hope that readers can understand what is at the heart of the marriage of the two reli[1]gions. So that marriage is not closed to external matters but is open to happi[1]ness of the couple. The method used in this study is qualitative data obtained from the library. The authors examine the data obtained and analyze and provide continuity in conclusion. The results obtained are the achievement of views on welfare in the Catholic and Islamic marriages.